PT PERTAMINA MOR VI’S STRATEGY TO FACE ASPHALT IMPORT PROHIBITION - Yuliana, Indah; Linando, Jaya Addin (Jurnal Manajemen Bisnis, 2024)
This research was conducted because of the import prohibition phenomenon by the President of the Republic of Indonesia (RI), Joko Widodo, who stated that asphalt imports would stop in 2024. This phenomenon is fascinating because Indonesia also has a significant demand for asphalt compared to production. This phenomenon also impacts PT Pertamina MOR VI, a state-owned company involved in the asphalt business. This research was conducted to determine the strategy of PT Pertamina Marketing Operation Region (MOR) VI to deal with this phenomenon. Research data was collected through an interview process. The results obtained from the interview show that the first strategy implemented was to increase the limitations of the asphalt refinery at the Pertamina Refinery Unit IV and asphalt production on Buton Island. After overcoming production limitations, PT Pertamina MOR VI focused on setting national product prices based on the Argus Asphalt Index, Opex, and sales margins to compete with global asphalt prices and competitors. The final strategy is how PT Pertamina MOR VI maintains and increases its asphalt marketing market share among agents. These three strategies effectively overcome the effect of asphalt import prohibition in 2024.